P218 Determining the neurocognitive status and functional ability to screen for HIV-associated neurocognitive disorder (HAND). (14th July 2019) - Agarwal, Ritika; Aujla, Ravinder; Gupta, Amit; Kumar, Mukesh
Abstract : Background: To adequately evaluate the extent of neurocognitive impairment in PLHIV, a battery of neuropsychological tests is typically administered which are neither cost effective nor time efficient in the outpatient clinical setting. The aim of the study was to assess neurocognitive status and functional ability of people living with HIV and find a brief screening tool to identify those who would benefit from a full diagnostic evaluation. Methods: The study enrolled 160 Patient living with HIV (PLHIV) (80 pre-ART and 80 On-ART) fulfilling the inclusion and exclusion criteria from March 2014 to January 2019. Neurocognitive assessment and an assessment of Functional ability was done by using the Montreal Cognitive Assessment (MoCA) and Lawton and Brody IADL Scale respectively. Results: The study population consisted of 75.6% males and 24.4% females with mean age of 44±10 years. All of the subjects were literate (61.2% subjects had received up to High school level education) and 76.2% were married. The mean duration of HIV infection among ART naive PLHIV and those on ART was 2±1.33 years and 3±2.10 years respectively. The overall prevalence of HAND in the study subjects was 52.5%. Of these, 47.5% had ANI and 5% had MND. In MoCA, the most frequently affected domains were Language (97.6%), visuospatial ability (92.9%) and memory (71.4%). Conclusion: The prevalence of HAND in both groups were similar suggesting that neurocognitive impairment starts early in HIV infection. Older age (>40 years) and fewer years of formal education were statistically associated with the presence of HAND. HAND involves both cortical and subcortical regions of the brain. Memory and Visuospatial function impairment had the most predictive potential for detecting the presence of HAND. HAND screening is recommended in all PLHIV at enrolment into care. Simple tools like MoCA can be used in busy outpatient settings by healthcare workers to screen for HAND. Disclosure: No significant relationships.